Concurrent application and artificially intelligent target selection - Grimal, Francis; Pollard, Michael J. (Journal on the use of force and international law, 2024)
This article explores the alleged use by Israel of its controversial AI targeting system, 'Lavender,' to frame a broader research question as to whether such a system complies (or not) with both the ad bellum and the in bello frameworks. Though this article does not seek to address the sensitive issues in Gaza directly, it instead examines how such a system could operate within both realms. The authors emphasise the importance of concurrent application, where ad bellum and in bello principles are simultaneously implemented in target selection. They argue that for an in bello system like Lavender it is crucial to integrate ad bellum considerations to ensure compliance with ad bellum proportionality and necessity under the UN Charter & customary international law. The authors underline that any in bello AI system used in self-defence must incorporate ad bellum factors, and maintain that concurrency is essential and non-negotiable where ambiguity exists.